Pediatric Emergency Medicine Simulation Curriculum: Septic Shock - Jennifer Reid; Kimberly Stone (Association of American Medical Colleges, 2013)
Abstract Septic shock continues to be a major cause of morbidity and mortality in children. Early recognition and management of severe sepsis and septic shock in the first hour of resuscitation have been shown to decrease mortality. Medical providers must recognize children in septic shock early precisely because they are more likely to respond favorably to treatment. The goal of this scenario is to provide the learner with an opportunity to manage life-threatening pediatric septic shock, where the correct steps need to be taken in a limited period of time. This resource provides a comprehensive package to support instructors teaching pediatric septic shock. It includes background knowledge, presimulation preparation guidelines, a simulation scenario, tools to help evaluate team performance and guide debriefing, tools to elicit student feedback on the instructor's performance, and supplemental educational materials for instructors to provide their students. Also included are extensive preparatory material, to help the instructor prepare the environment and learners. The debriefing tools, have been tailored specifically for this scenario, with advice on how the instructor can tailor them to different learners. This resource will help support standardization of the teaching process, helping simulation instructors maximize their impact. Supplemental learner handouts can help reinforce the teaching points even after the session has finished. The inclusion of a learner feedback form supports the instructor's ongoing growth while helping faculty to document their teaching efforts.